(untitled) (Journal of Engineering, 2006)
This paper presents a modified Newton method of load flow analysis for radial distribution systems. It is derived with the Jacobian matrix is in UDUT form, where U is a constant upper triangular matrix depending solely on system topology and D is a block diagonal matrix. With this formulation, the conventional steps of forming the Jacobian matrix, LU factorization and forward/back substitution are replaced by back/forward sweeps on radial feeders with equivalent impedances. The method has advantages over Newton’ s method in terms of speed of solution (no. of iterations), and reliability of convergence by inserting a minimization technique (Cubic Interpolation Technique). The algorithm exhibits a control of the convergence. As such the method converges for cases when conventional Newton’ s method and some other popular methods diverge. Two large distribution systems of 490 nodes and 722 nodes with different r/x ratio in line impedance are used to examine the performance of the method. These tests have shown that the proposed method is as robust and efficient as the forward/back sweep method. The proposed method can be extended to the solution of three phase unbalanced representation.